Hydrography of the Eastern Mediterranean basin derived from argo floats profile data. (January 2020) - Kassis, Dimitris; Korres, Gerasimos
Abstract: As the Eastern Mediterranean integrates different sub-basins with important hydrological features, during recent decades it has often become a target of study by the oceanographic community. The recent expansion of observational tools and methods in the marginal seas has allowed more enhanced studies of the oceanographic processes that dominate such areas. In this work, temperature and salinity profile data collected by Argo floats in the Eastern Mediterranean are analysed for the period 2004–2017. The spatio-temporal variability of the basin's physical properties, together with the depicted changes in the different sub-basins, is investigated in an attempt to construct the latest hydrographic picture of the region. The findings describe the dominant water masses and reveal a general positive trend in the basin's thermohaline properties. The inter-annual variability of the stored heat and salt, and their distribution in the water column, reveals strong climatic signals that are dominated by previously reported alternations of the general circulation and convection events in the area. The latter are correlated with the surface temperature and salinity fields and are traced within the area's different sub-basins. In the early period (2004–2010), data from Levantine and Ionian depict inter-annual variability of the upper layers salinity field that is correlated with previously reported alternations of the Levantine's circulation, and intermediate water production in the Ionian. During the latest period (2012–2017), when the data coverage is denser and more representative for the wider area of the Eastern Mediterranean, the Adriatic sub-basin presents intense dense water production activity while the Aegean Sea undergoes a relaxation period with significant variability at intermediate layers due to water mass exchanges.